Strategi Peningkatan Ekonomi Masyarakat Desa Cinangsi melalui Diversivikasi Produk Olahan Buah Sawo - Silvi Nurianah, Silvi; Suryopratomo, Anggit; Lestari, Tia Astiani; Agus, Eka Agus F (Ma'soem University, 2025)
Cinangsi Village has abundant local agricultural potential, especially sapodilla fruit, which is available almost year-round. Until now, its utilization has been limited to fresh sales with low economic value, so a product diversification strategy is needed to increase competitiveness and added value. This study aims to examine the processing of sapodilla into dodol (a traditional Indonesian snack) as a superior village product that can strengthen local culinary identity. The activity method used is PAR (Participatory Action Research) through three stages: Planning, Implementation, Results, and Evaluation. The results of this community service activity can be an innovation in providing new business opportunities for housewives and MSMEs. The results achieved show an increase in skills in processing sapodilla fruit into sapodilla dodol products, which have a longer shelf life and wider market potential than fresh fruit. Thus, diversification of processed sapodilla products into dodol can be an effective strategy in increasing the economic independence of the Cinangsi Village community in a sustainable manner.